Tinjauan Yuridis Pelaksanaan Perjanjian Kredit Pemilikan Rumah (Studi Kasus Pt Kandang Karya Perkasa Di Sukoharjo) - Mentari, Eka; , Septarina Budiwati, S.H., M.H (2016)
This study aims to identify and describe the legal construction and problems that arise in the purchase agreement houses on credit is done in PT. Kandang Karya Perkasa in Sukoharjo. The method used is empirical juridical with descriptive research. The data source consists of primary data is the result of interviews and secondary data is data of primary and secondary law. Data were collected by interview, observation and then analyzed qualitatively. The results showed that the legal construction home purchase agreement on credit at PT. Kandang Karya Perkasa in the form of a deed of sale that is authentic in which the agreement is implemented and validated before a notary. The problems most often arise is the default form of breakdown of repayment by the debtor to the creditor that is solved by preventive measures by way of supervision, coaching and binding credit guarantee, is being repressively with the sale or auction of the collateral is done according to the procedures applicable under the law and according to the agreement which has been done.